¿Objetivismo o subjetivismo? La teoría hilemórfica del precio de Francisco de Vitoria como salida de un falso dilema - Schwember Augier, Felipe (Cauriensia, 2024)
The current work attempts to explain Francisco de Vitoria’s theory of just price by making an analogy with hylemorphic theory. Working with this analogy, we maintain that Vitoria’s just price theory concurs with subjective and objective factors, which serve as the form and material of the price, respectively. We maintain that while objective factors perform a purely descriptive function in that they help explain the actual price that a good has, subjective factors also play a normative function to the extent that they explain how these factors should be formed. More specifically, we defend the position that the subjective factors expressed in the "common estimation" to which Vitoria refers should be considered the only normative criteria that are relevant when it comes to determining a just price. The reason is that the existence of a common estimation guarantees that no party be able to take advantage of the necessity of any other or-which is the same thing-the intent of any party find itself encumbered by necessity.